New possibilities of polarization-sensitive optical coherence tomography using geometric phase approach for diagnostics of thin surface (subsurface) biological layers - Zenkova, Claudia; Ivanskyi, Dmytro; Angelsky, Oleg (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
The paper focuses on presenting the new original results and highlighting of possibilities of geometric phase using in low-coherence polarization-sensitive tomography tasks for noninvasive diagnostics of surface (subsurface) layers of transparent (translucent) biological media (samples and tissues). Determination of the object fields’ geometric phase in the modified Mach–Zehnder interferometer allows one to reproduce the geometric structure (optical axis/collagen orientation) of birefringent biological medium. Polarization-interference noninvasive approach of the collagen orientation structure diagnostics of thin nanosized surface tissue layers is proposed at the first time. It is shown, that taking into account the information about top (surface) layer structure can significantly improve the accuracy of deeper (subsurface) layers parameters estimation. The proposed solution is a unique feature that is not accessible in classical polarization-sensitive techniques of information recovery on tissue structure.
Optica Applicata, Vol. 54, 2024, nr 3, s. 303-316
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; polarization-sensitive optical coherence tomography; geometric phase; anisotropic biological tissue; surface (subsurface) layers; birefringence; optical axis orientation